1995
DOI: 10.1136/vr.137.7.158
|View full text |Cite
|
Sign up to set email alerts
|

Development of a diagnostic approach to the identification of rabbit haemorrhagic disease

Abstract: Haemagglutination and ELISA tests, and negative contrast electron microscopy, have been used to identify rabbit haemorrhagic disease virus in naturally occurring cases of the disease and in experimentally infected rabbits in the United Kingdom. Haemagglutination tests alone are not satisfactory for the diagnosis because non-haemagglutinating isolates of the virus, otherwise indistinguishable from others, have been found in some outbreaks. Haemagglutination inhibition tests have shown that a proportion of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 0 publications
4
36
0
Order By: Relevance
“…Evidence of this is the emergence of the decreasingly homogenous new strains with altered antigenic and genetic features, showing different tropism and pathogenicity for the target species. The strains detected in relatively short period of time, which demonstrate new characteristics, vide phenotypic HA-negative RHDV variant, antigenic and genetic RHDVa variants, and the new American and French RHDV variants, are examples of this phenomenon (5,6,8,17,24,27,34,36). This may be due to the effect of environment, the use of vaccination, or the process of evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of this is the emergence of the decreasingly homogenous new strains with altered antigenic and genetic features, showing different tropism and pathogenicity for the target species. The strains detected in relatively short period of time, which demonstrate new characteristics, vide phenotypic HA-negative RHDV variant, antigenic and genetic RHDVa variants, and the new American and French RHDV variants, are examples of this phenomenon (5,6,8,17,24,27,34,36). This may be due to the effect of environment, the use of vaccination, or the process of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the presence of the classic form of RHDV strains with an altered haemagglutination (HA) profile (phenotypic HAnegative variant), RHDV strains known as antigenic and genetic variants (RHDVa), a moderately pathogenic calicivirus (MRCV), a recently new French RHDV variant, and non-pathogenic caliciviruses (RCV, RCV-A1, Lambay, 06-11) (1,4,5,6,24,26,27,34,36). Pathogenic RHDV and RHDVa isolates belong to one serotype (2,3,10,36).…”
Section: Introductionmentioning
confidence: 99%
“…RHDV strains isolated in the field are generally highly lethal (up to 95% mortality 2 days post-infection) and transmissible, but interestingly the impact of the virus has been highly contrasted. Some populations have a high proportion of seropositive rabbits in the absence of recorded mass mortality due to the m a n u s c r i p t 5 disease (Chasey et al, 1995;Cooke et al, 2000;Marchandeau and Boucraut-Baralon, 1999;Marchandeau et al, 1998;Rodak et al, 1990;Sanson et al, 2000;Trout et al, 1997),…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks killed 140 million farmed rabbits in China in 1984 [7], 64 million farmed rabbits in Italy in 1986 [8] and 30 million wild rabbits in Australia in just a few weeks following its release in 1995 [6]. However, immunity to RHDV has been found in the absence of signs of disease in both wild and captive populations from a number of locations, including the former Czechoslovakia, Switzerland, Austria, Germany and Sweden [9][10][11][12][13]. Seroprevalence was particularly high in the United Kingdom, with a mean of 64 % and a maximum of 100 % [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Seroprevalence was particularly high in the United Kingdom, with a mean of 64 % and a maximum of 100 % [14,15]. It has been proposed that this immunity may be due to a non-pathogenic strain of RHDV [10][11][12][13][14], such as that isolated from a rabbitry in Italy in 1996 [9,16].…”
Section: Introductionmentioning
confidence: 99%